Integration of Virtual Simulation of Traditional Kekehan Games on The Material of Moment of Inertia and Angular Momentum - Damarsha, Adrian Bagas; Saputra, Oka; Suprapto, Nadi; Hariyono, Eko; Nisa’, Khoirun (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective: The curriculum in Indonesia emphasizes learning with the 5.0 society era approach. The era of society emphasizes learning that is integrated with social culture. But in fact it is difficult to implement because students do not know the visualization of the concepts and problems discussed. Therefore, it is necessary to develop learning media that can provide visualization of problems and integrated social culture. Method: The method used is RnD with 3D design (Define, Design, Development) and the last stage of evaluation Results: The results obtained from this study are virtual simulation media integrated with traditional kekehan games getting a very valid criteria score. The results of students' responses show that virtual simulation media can already help students in helping physics problems. The evaluation results for improvement are related to the visualization of animation for kekehan so that it can move in the concept of moment of inertia and angular momentum. Novelty: Therefore, the purpose of this study was to analyze the validation of virtual simulation media integrated with traditional kekehan games and the response of students after using virtual simulation media integrated with traditional kekehan games